Penerapan Keselamatan Dan Kesehatan Kerja Dalam Praktik Instalasi Penerangan Listrik Di Sekolah Menengah Kejuruan - Hilda Ashari; Dessy Ana Sari (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2023)
This research is a descriptive research in the form of a pre-experiment which is not yet a serious experiment. This study aims to describe the application of Occupational Safety and Health (OSH) in the practice of electric lighting installations at SMKN 2 Makassar and the factors that hinder the application of OSH. This study used a design (the-one group posttest-design). Data collection techniques used are observation, interviews and documentation. Based on the results of the study, it can be concluded that through the first observation, the application of K3 in the practice of installing electric lighting is still lacking because there are several aspects that have not been implemented. Data on the percentage level of conformity to the observed aspects are included in the medium category. After providing an understanding of OSH, a second observation was carried out where the application of OSH had increased so that the results of the percentage data on the level of conformity to the observed aspects were included in the good category. There are inhibiting factors for the application of OSH, namely that the teacher has not given directions optimally regarding the importance of implementing OSH, as well as directions to always pay attention to the use of personal protective equipment during practice.